E‐band high aperture efficiency reflector antenna with adjustable beamwidth. Issue 11 (27th July 2021) - Jiang, Hang; Yao, Yuan; Xiu, Tao; Cheng, Xiaohe; Wang, Caixia; Yu, Junsheng; Chen, Xiaodong
Abstract: This paper presents an E ‐band axial displaced ellipse (ADE) reflector antenna with the characteristics of both high aperture efficiency and adjustable beamwidth. Optimization of slightly shaping the subreflector is adopted for a higher aperture efficiency of the entire antenna. Defocusing effect of moving the subreflector can effectively increase the beamwidth, and half‐power beamwidth (HPBW) is adjusted by axially moving the subreflector. The reflector antenna is simulated, fabricated and measured. The aperture efficiency is increased to approximately 75% after optimization. The measured gain of 45.6 ± 1 dBi from 71 to 86 GHz agrees well with the simulation. Also, the measured HPBW achieves an increase of more than five times changing from 0.88° to 4.4° at 71GHz, 0.86°‐ 5° at 86GHz. It is the first time to achieve high aperture efficiency ADE reflector antenna with adjustable beamwidth, which is of great significance for compact aircraft antenna applications.